ESTETIKA BATIK TE LEBONG SEBAGAI INSTRUMEN LITERASI VISUAL DI SD NEGERI 67 LEBONG - Rieke Novela; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the utilization of Batik Te Lebong aesthetics as a visual literacy instrument in SD Negeri 67 Lebong. The research background is based on the limited understanding of students regarding local cultural symbols, despite visual literacy being a crucial skill in the digital era. The study employed a qualitative descriptive method, involving fifth-grade teachers and students as participants. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, presentation, and conclusion drawing. The findings reveal that Batik Te Lebong enhances student engagement, strengthens their ability to interpret visual symbols, and fosters pride in local culture. Students were able to write descriptive narratives, redraw batik motifs, and connect symbols with cultural values. Teachers benefited from contextual and relevant teaching media. The study concludes that Batik Te Lebong is effective as a medium for visual literacy and serves as a means of preserving local culture in primary education.